Análisis de los parámetros fisicoquímicos y biológicos en sistema de producción de chame (Dormitator latifrons), zona centro norte de la provincia de Manabí - Santana Vera, Anthony Jahir (2024)
The research in the north-central area of Manabí on the chame production system adopted an exploratory-descriptive approach in two main phases: the georeferencing and characterization of the production systems, and the evaluation of physicochemical and biological parameters of the water in the culture pools. 30 systems were identified in the cantons Tosagua and Chone, mostly semi-intensive with the use of well water and earthen ponds. The fattening phase predominated, using oxygenation methods such as natural cascades. Production is mainly intended for local sales and export. Monitoring revealed diurnal pH fluctuations between 7.60 and 7.76, more pronounced in pool 1, with total dissolved solids between 1900 and 2000 mg/L. The electrical conductivity was 3.75 to 4.10 mS/cm, high compared to freshwater, and the water temperature ranged from 27 to 31 °C. Dissolved oxygen ranged from 4 to 8 mg/L, with levels highest in the afternoon. Turbidity remained below 50 NTU, with peaks in April and May. Other parameters such as salinity, alkalinity, nitrites, phosphates, total hardness, biological oxygen demand and total coliforms were evaluated. The manual of good practices focused on improving sustainability and productivity offers guidelines from water management to harvesting and sanitation. In conclusion, the research in the north-central area of Manabí highlights the importance of implementing sustainable and effective practices in water management and pool management.